Linking consumer confidence index and social media sentiment analysis - Shayaa, Shahid; Ainin, Sulaiman; Jaafar, Noor Ismawati; Bahri, Shamshul; Phoong, Seuk Wai; Yeong, Wai Chung; Al-Garadi, Mohammed Ali; Muhammad, Ashraf; Piprani, Arsalan Zahid (Cogent OA, 2018)
This study aims to analyse the link (correlation) between and the official CCI and social media big data (via sentiment analysis) on consumer purchasing behaviour for two types of products over the course of two years (24 months, from January 2015 to December 2016). The CCI data was obtained from the Malaysian Institute of Economic Research (MIER) while the sentiment analysis was obtained from twitter. The results indicate that there is a significant but very small relationship between CCI and social media sentiment analysis. On the basis of the results we conclude that social media can offer huge a huge volume of data on consumer confidence, the analysis of which can be conducted at a more rapid time and integrated with existing methods in a synergistic way to refine the accuracy of the CCI using data from far larger populations.